2021
DOI: 10.3390/antiox10071092
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fucoxanthin Dampen Pathogen-Associated Molecular Pattern (PAMP) Lipopolysaccharide-Induced Inflammatory Action and Elevated Intraocular Pressure by Activating Nrf2 Signaling and Generating Reactive Oxygen Species

Abstract: Inflammation and oxidative stress are closely related processes in the pathogenesis of various ocular diseases. Uveitis is a disorder of the uvea and ocular tissues that causes extreme pain, decreases visual acuity, and can eventually lead to blindness. The pharmacological functions of fucoxanthin, isolated from brown algae, induce a variety of therapeutic effects such as oxidative stress reduction and repression of inflammation reactions. However, the specific anti-inflammatory effects of fucoxanthin on patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…PRDX3 encodes a mitochondrial protein with antioxidant function [ 9 ]. Research have shown that oxidative stress plays a vital role in the progression of uveitis [ 5 ]. Thus, we selected PRDX3 for functional verification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRDX3 encodes a mitochondrial protein with antioxidant function [ 9 ]. Research have shown that oxidative stress plays a vital role in the progression of uveitis [ 5 ]. Thus, we selected PRDX3 for functional verification.…”
Section: Resultsmentioning
confidence: 99%
“…Although the etiology of uveitis remains largely unknown, strong evidence has shown that uveitis is associated with oxidative stress [ 5 , 6 ]. Accumulated reactive oxygen species (ROS) including hydrogen peroxide (H 2 O 2 ) can disrupt retinal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In studies with an animal model, the administration of fucoxanthin to ovalbumin-induced asthma mice resulted in decreased intracellular ROS formation and increased antioxidant enzyme activity [ 32 ], and in alcoholic liver injury mice yielded elevated levels of liver total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT), probably through the activation of the Nrf2-mediated antioxidant pathway [ 9 ]. A similar Nrf2-mediated antioxidant pathway was further characterized by Chen et al [ 33 ] when fucoxanthin was administered in LPS-induced uveitis rats, in addition to increased SOD and decreased malondialdehyde (MDA). Chiang and the team experimented on diabetic retinopathy in human retinal epithelial cells that showed protective effects of fucoxanthin to increase the antioxidant enzyme activity and decrease ROS levels, probably through the strong antioxidant activities of Nrf2 activation [ 23 ].…”
Section: Resultsmentioning
confidence: 67%
“…In another study investigated by Chiang et al [ 23 ], diabetic retinopathy induced by Glucose- and 4-Hydroxynonenal (HNE) in human retinal pigment epithelial cells, fucoxanthin showed protective effects by reversing cell damage, inflammatory response, cell adhesion factor protein expression, and apoptosis through the modulation of Nrf2 signaling pathways. The lipopolysaccharide-induced uveitis rats model has been reported to have similar ocular protective Nrf2 signaling pathways by fucoxanthin, as characterized by increased SOD level, and decreased MDA level, inflammatory cells, TNF-α concentrations, and corneal endothelial disruption [ 33 ]. Accumulating scientific evidence suggests that fucoxanthin is a potent dietary carotenoid with antioxidant and anti-inflammatory potentials to protect eyes against injuries.…”
Section: Resultsmentioning
confidence: 99%
“…Alcoholmediated oxidative injury and inflammation were ameliorated by FX through activation of Nrf2 and suppression of TLR4-induced NF-κB signaling [301]. Promotion of Nrf2 and SOD and suppression of TNF-α action were implicated in ameliorating pathogen-associated molecular pattern-induced inflammation by FX [302]. A recent review reported that signaling pathways like PI3K/AKT/Nrf2, ERK, AMPK/AKT/cAMP response element binding protein (CREB)/peroxisome proliferator-activated receptor-gamma coactivator-1α (PGC-1α), and Nrf2-autophagy were involved in FX-induced anti-inflammatory response [303].…”
Section: Fucoxanthin (Fx)mentioning
confidence: 99%